(untitled) (Research, Society and Development, 2022)
In Brazil, Legal Reserve Areas (ARLs) are intended to maintenance of biodiversity and ecological processes, but can economically exploit the sustainable way. To restoration and use of these degraded spaces, are recommended the biodiverse agroforestry systems (SAF), that are identified as sustainable, as they provide both ambiental and socioeconomic benefits. The objective of this work is to propose two arrangements of agroforestry systems, with socioeconomic viability, in the ecotone between Cerrado and Atlantic Forest and in the Cerrado biome, aiming to comply the Brazilian Forest Code and subsidize farmers to restore these environmental liabilities, produce food and generate income in these areas. A multidisciplinary study was carried to indicate the native tree and shrub species, as well as the species intended for income generation and the respective designs for each of the SAF, the estimates of production, commercialization and income generation. For analysis of economic viability, we used techniques for evaluating capital investments such as: Net Present Value, Internal Rate of Return, Uniform Equivalent Annual, Payback, Profitability Index, Modified Internal Rate of Return, Benefit/Cost ratio and Asset pricing model financial, where data on income and expenses were inserted that reflect the reality of family farming, verifying its profitability over 20 years. The results showed that biodiverse agroforestry systems can be adopted by farmers to implement the "productive recovery" of Legal Reserve Areas, generating income from the first year after its implementation, maintaining itself over time.